Relationship between RPE and choriocapillaris in age-related macular degeneration - McLeod, D Scott; Grebe, Rhonda; Bhutto, Imran; Merges, Carol; Baba, Takayuki; Lutty, Gerard A (Investigative ophthalmology & visual science, 2009)
The purpose of this study was to examine the relationships between choriocapillaris (CC) and retinal pigment epithelial changes in age-related macular degeneration (AMD). Morphologic changes in the retinal pigment epithelium (RPE)/choriocapillaris complex were quantified in dry and wet forms of AMD, and the results were compared with those in aged control eyes without maculopathy. Postmortem choroids from three aged control subjects, five subjects with geographic atrophy (GA), and three subjects with wet AMD were analyzed using a semiquantitative computer-assisted morphometric technique developed to measure the percentages of retinal pigment epithelial and CC areas in choroidal wholemounts incubated for alkaline phosphatase activity. The tissues were subsequently embedded in methacrylate and were sectioned so that structural changes could be examined. There was a linear relationship between the loss of RPE and CC in GA. A 50% reduction in vascular area was found in regions of complete retinal pigment epithelial atrophy. Extreme constriction of remaining viable capillaries was found in areas devoid of RPE. Adjacent to active choroidal neovascularization (CNV) in wet AMD, CC dropout was evident in the absence of retinal pigment epithelial atrophy, resulting in a 50% decrease in vascular area. Lumenal diameters of the remaining capillaries in wet AMD eyes were similar to those in control eyes. The primary insult in GA appears to be at the level of the RPE, and there is an intimate relationship between retinal pigment epithelial atrophy and secondary CC degeneration. CC degeneration occurs in the presence of viable RPE in wet AMD. The RPE in regions of vascular dropout are presumably hypoxic, which may result in an increase in VEGF production by the RPE and stimulation of CNV.